Primary monophasic synovial sarcoma, a rare pulmonary mesenchymal neoplasm: report of a case with review of literature - Lakshmi, A. Bhagya; Sri, K. Satya; Kartheek, B. V. S.; Rao, Nagarjun (International Journal of Research in Medical Sciences, 2017)
Synovial sarcoma is an uncommon malignant soft tissue tumour which occurs primarily in young adults. It most commonly occurs in the extremities near large joints, particularly the knee joint. Primary pulmonary synovial sarcoma has only occasionally been reported in the literature. We report a case of primary pulmonary monophasic synovial sarcoma in a 23 year old male patient presenting with recent onset of hemoptysis, cough and expectoration. Although an uncommon primary site, the characteristic histological and immunohistochemical features, and fluorescence in situ hybridization analysis for the characteristic (X;18) translocation, with thorough clinical and imaging correlation allowed a definitive diagnosis of primary pulmonary monophasic sarcoma. The mainstay of treatment for these unusual tumours remains complete surgical excision followed by adjuvant radiation and/or chemotherapy.